ALP-functionalized Mesoporous Silica Nanoparticles for Antibody Labeling in Immunosensors - Kovářová, Aneta; Čadková, Michaela; Dvořáková, Veronika; Bílková, Zuzana; Korecká, Lucie (BEST Servis, 2016)
Currently, the new ways how to improve the sensitivity of commonly used ELISA methods for detection of biomarkers are being found. The possibility how to achieve lower detection limits is the use of secondary antibodies labeled with nanoparticles modified by enzymes instead of antibodies labelled only by enzymes. Here we present ALP-modified silica mesoporous nanoparticles utilized for labelling of anti-ApoE IgG antibodies for quantification of apolipoprotein E (ApoE) by sandwich-type magneto-imunosorbent enzyme assay combined with square wave voltammetry. In this arrangement we achieved linear calibration curve in the concentration range of 75 – 500 ng/ml.
Alkalickou fosfatázou funkcionalizované mezoporézní silika nanočástice pro značení protilátek v imunosenzorech
Keywords: Alkaline phosphatase; Silica nanoparticles; Antibody labeling; Electrochemical immunosensors; SWV; Alalická fosfatáza; Silika nanočástice; Značení protilátek; Elektrochemické imunosenzory; SWV